Engineering the link: from genome interaction maps to functional insight - Petersen, Frido; Westermann, Simon; Smialkovska, Valeriia; Mathony, Jan; Feldmann, Angelika; Niopek, Dominik (Advanced biology, 2025)
The 3D organization of the genome constitutes a spatial layer of information processing that helps govern gene expression and thus cell function. Advances in chromosome conformation capture sequencing have enabled detailed assessment of chromatin architecture, from enhancer-promoter loops to topological domains and higher-order contacts, across cell types and developmental states. While the ability to investigate genome conformation is maturing, the field faces a central challenge: The link between chromatin interactions and cellular function remains largely correlative, leaving their causality unresolved. This review explores how recent developments in genome engineering enable the targeted manipulation of 3D chromatin architecture - specifically DNA loops - to illuminate causal links between genome structure and function. Synthetic strategies are introduced that rewire enhancer-promoter communication through engineered chromatin loops, leveraging programmable DNA-binding platforms such as zinc fingers, transcription activator-like effectors (TALEs), and CRISPR-Cas9. The current limitations of these approaches related to efficiency, scalability, and specificity are also highlighted, and the strategies to address them are outlined. As these systems mature, programmable 3D genome engineering is emerging as a transformative pillar of synthetic biology, complementing sequence-based editing as a core modality for both understanding and ultimately reprogramming genome function.
Online verfügbar: 12. November 2025
Gesehen am 20.02.2026
Keywords: Rezension